Hypomethylating therapy mitigates acute allograft rejection in a murine lung transplant model - Yarnoff, Kristine M.; Daccarett-Bojanini, William N.; Villabona-Rueda, Andres F.; Sollmann, Manuel; D’Alessio, Franco R.; Dodd-o, Jeffrey M. (Frontiers in Transplantation, 2025)
IntroductionAcute cellular rejection of transplanted lung allografts involves activated cytotoxic T cells and reduced Regulatory T (Treg) cell function. Calcineurin inhibitors, the cornerstone of immunosuppressive regimens, suppress T cell cytotoxicity but inhibit Treg proliferation. The DNA hypomethylating agent decitabine (DAC) can abrogate T cell cytotoxicity while stimulating Treg proliferation.MethodsWe sought to determine the effects of DAC treatment in a murine MHC-mismatched orthotopic lung transplant model.ResultsRescue treatment with DAC maintains lung allograft gross and histologic integrity with a reduction in cytotoxic T cell responses. CD4+FoxP3+ T cell depletion in Foxp3DTR mice exacerbated rejection lung injury compared to CD4+FoxP3+ T cell sufficient mice and failed to abolish the protective effect of DAC in this model. The protective effect of DAC was associated with a reduction in cytokine production from host T-cells.DiscussionDecitabine could offer a new line of treatment for acute lung allograft rejection, in part via its effects on Tregs.